PENGEMBANGAN BUKU AJAR DENGAN GAYA BAHASA LOKAL SEHARI-HARI SUMBA BARAT DAYA PADA MATERI PERSAMAAN GERAK UNTUK PEMBELAJARAN FISIKA SISWA KELAS XI SMA - Elyakim Nova Supriyedi Patty; Mikael Sene (SekolahTinggi Keguruan dan Ilmu Pendidikan (STKIP), 2017)
This development research is aimed to producing physics textbooks which is appropriate to the local language (mother tongue) in Southwest Sumba about motion equations into Senior High School students Grade XI which affects the students' activity in learning. This study was conducted to find out the textbook that is produced based on aspects of validity, practicality and effectiveness. The type of this research is a development study. This study was conducted by using R and D (Research and Development) method through procedures of defining potentials and problems, collecting information, designing products, validating designs, improving designs, testing products, revision productss in preliminary research, and research. Subjects of this research are 23 students in students Grade XI SMAN Loura Sumba Southwest academic year 2016/2017. From the results obtained that the textbook developed has met the valid criteria with an average of 75.9 was in good criteria, practicality of the teacher's book according to the teacher it was in the good category of the average value 78, the practicality of textbooks according to the students has mean value in average 85.96 was in the very good category, whereas there is a significant difference between the learning results before and after the use of textbooks with the local language style of Southwest Sumba. So, it can be concluded that the textbooks with the local language style of Southwest Sumba can improve the students learning results and effectively used in physics learning with an average rating is a very good value of 92.6Keywords: textbooks, development research